1979
DOI: 10.1159/000153032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies on the Kolams of Andhra Pradesh, India

Abstract: A total of 220 persons belonging to the Kolam tribe in the Adilabad District of northwest Andhra Pradesh have been tested for 18 red cell enzyme systems and for haemoglobin. Generally, the gene frequencies for the systems which showed electrophoretic variation were within the range for Indian populations; the gene frequency for AK1 is high by Indian standards and Hb AS is present. LDH Calcutta 1 was not detected in this population and a single example of PHI 2-1 was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
5
11
1
Order By: Relevance
“…The ESD 2 alMe frequency ranges between 0.2448 in the Raj Gond of Maharashtra and 0.3989 in the Paroja of Orissa. The present allele frequencies of ESD 2 remain within the range of reported allele frequencies among Indian tribes which show a wide range of variation, that is lowest ESD 2 (0.022) among the Gaddi Rajput of Himachal Pradesh (Singh et al, 1982) and a highest (0.475) is in the Kolam of Andhra Pradesh (Ramesh et al, 1979). In general, there has been a gradual decline of ESD 2 allele from east to west direction except for a few transient elevation among the Bhatra of Bastar and among the Paroja of Koraput districts.…”
Section: The Distributionsupporting
confidence: 76%
“…The ESD 2 alMe frequency ranges between 0.2448 in the Raj Gond of Maharashtra and 0.3989 in the Paroja of Orissa. The present allele frequencies of ESD 2 remain within the range of reported allele frequencies among Indian tribes which show a wide range of variation, that is lowest ESD 2 (0.022) among the Gaddi Rajput of Himachal Pradesh (Singh et al, 1982) and a highest (0.475) is in the Kolam of Andhra Pradesh (Ramesh et al, 1979). In general, there has been a gradual decline of ESD 2 allele from east to west direction except for a few transient elevation among the Bhatra of Bastar and among the Paroja of Koraput districts.…”
Section: The Distributionsupporting
confidence: 76%
“…Omoto and Blake (1972) described a similar variant in a Chinese of Singapore. In the present investigation no variant of type 2-1 was found, but there are reports of one example in each of the nontribal groups of Andhra and a frequency of the P G I ~ allele of 1.2~ from Christians of Kerala (Ramesh et al, 1979(Ramesh et al, , 1980Saha et al, 1976). This suggests localisation of the allele to specific populations of south India.…”
Section: A) the P G I 2 Allelecontrasting
confidence: 56%
“…In addition, dur ing recent years an increasing amount of work has been carried out on tribal popula tions in Andhra Pradesh [Rwo et al, 1978;Ramesh et al, 1979] and several further studies are currently in progress. Data on the ABO blood group system for Chenchus from the Farhabad Hills were presented by Maefarlane and Sarkar [1941], but the most important study was that of Simmons et al [1953] who reported extensive blood group data, secretor status and the ability to taste phenyl thiocarbamide for the Chenchu from the Guntur and Kurnool districts.…”
Section: Introductionmentioning
confidence: 99%